De restauratie van de Domtoren, verschillende restauratieopvattingen verenigd (Bulletin KNOB, 2010)
In 1899 the municipality of Utrecht decided upon a thorough restoration of the cathedral tower so as to restore it to its original state. However, the restoration committee led by the Roermond architect P.J.H. Cuypers (1872- 1922) could not complete the work in its original composition. The work took such a long time that in 1922 the committee came under the chairmanship of railway architect G.W. van Heukelom (1870-1952). Meanwhile the prevailing views on restoration were changing. Van Heukelom put an end to the rational Gothic style of Cuypers and continued the work in his own individual way. Whereas the original committee wanted to restore the tower to an almost ideal state, using historicizing forms and styles, Van Heukelom was looking for a way to restore the original character of the monument without reverting to the past. He made use of contemporary views on style and beauty. Van Heukelom was strongly influenced by H.P. Berlage and his vision that true beauty arose from society. Consequently, Van Heukelom gave his workmen a free rein. His restoration is characterized by the use of contemporary techniques and the use of brick. According to Van Heukelom the new elements had to be recognizable as such, but would have to be in harmony with the old parts as well. Consequently, the work of Van Heukelom is characterized by a large degree of austerity. The newly built reception building, for instance, is as much detached from the tower as possible, while at the same time the modern design is inspired by the tower. Various ‘generations’ of architects were involved in the restoration. Their different views on restoration are still visible in the monument.